Public Expenditure Review 1999 : Improving Education through Increased, Efficient, and Effective Utilization of Resources - Republic of Ghana (Tema Printing, Tema, Ghana, 2013)
The Governemnt of Ghana has been preparing public expenditure reviews annually since 1993, by adopting relevant thematic areas to highlight important issues of public expenditure management in Ghana. These reviews have indicated lapses in the mechanism through which public expenditures were made and also provided the basis for assessment of expenditure priorities of government. Since education is the largest spending sector of the economy, the 1999 public expenditure review is focused on improving the quality of education through increased efficient and effective use of resources. Under Ghana vision 2020, improving access to quality education in the country has been identified as one of the focal points for government to achieve its aim of ensuring efficient education in the country. Education and training are thus being structured to meet the current manpower needs of the country as well as satisfy the intellectual and skill requirement of a technology-based growing economy.